Cellulose ionics: switching ionic diode responses by surface charge in reconstituted cellulose films. Issue 19 (29th August 2017) - Aaronson, Barak D. B.; Wigmore, David; Johns, Marcus A.; Scott, Janet L.; Polikarpov, Igor; Marken, Frank
Abstract : Cellulose films as well as chitosan-modified cellulose films of approximately 5 μm thickness, reconstituted from ionic liquid media onto a poly(ethylene-terephthalate) (PET, 6 μm thickness) film with a 5, 10, 20, or 40 μm diameter laser-drilled microhole, show significant current rectification in aqueous NaCl. Abstract : Cellulose films as well as chitosan-modified cellulose films of approximately 5 μm thickness, reconstituted from ionic liquid media onto a poly(ethylene-terephthalate) (PET, 6 μm thickness) film with a 5, 10, 20, or 40 μm diameter laser-drilled microhole, show significant current rectification in aqueous NaCl. Reconstituted α-cellulose films provide "cationic diodes" (due to predominant cation conductivity) whereas chitosan-doped cellulose shows "anionic diode" effects (due to predominant anion conductivity). The current rectification, or "ionic diode" behaviour, is investigated as a function of NaCl concentration, pH, microhole diameter, and molecular weight of the chitosan dopant. Future applications are envisaged exploiting the surface charge induced switching of diode currents for signal amplification in sensing.